Innovative Work Behavior of Santri: The Influence of Proactive Personality and Boarding School Climate - Akhmad Baidun; Farhanah Murniasih; Rusdi Hamka Lubis; Arisya Ghina; Rena Latifa; Moh. Irvan (Tazkiya Journal of Psychology, 2024)
Islamic boarding schools as Islamic education institutions in Indonesia have an important role in developing students holistically. Santri in addition acquire religious knowledge but must also be able to adapt to the times. For this reason, innovation and proactive behavior are the qualities needed by santri. An adequate boarding school environment should support the innovation of students, and the school climate in the boarding school has an important role in this. Islamic boarding schools also have a uniqueness in shaping the behavior of students by emphasizing the religious and moral character of Islam. Fulfillment of a comfortable school climate in Islamic boarding schools is important to achieve this goal. This study aims to examine the effect of proactive behavior and the school climate on santri’s innovative work behavior. The sampling technique uses non-probability sampling with purposive sampling technique. Data collection used three questionnaires consisting of an innovative work behavior scale, a proactive personality scale and an organizational climate scale. Data analysis was performed using multiple regression analysis. A total of 219 santri at Boarding school Gontor participated in this research, as a pesantren known for its characteristics and potential for developing student innovation. The results indicate that there is a significant effect of proactive behavior and the school climate for santri’s innovative work behavior (sig < .05) and the proportion of variance by 14.9%. Suggestion implications, there is a need for the development of proactive behavior programs among santri and the creation of a physical and psychological environment within Boarding school that supports santri innovation.